1999
DOI: 10.1101/gad.13.9.1079
|View full text |Cite
|
Sign up to set email alerts
|

FILAMENTOUS FLOWER, a meristem and organ identity gene of Arabidopsis, encodes a protein with a zinc finger and HMG-related domains

Abstract: Distinctive from that of the animal system, the basic plan of the plant body is the continuous formation of a structural unit, composed of a stem with a meristem at the top and lateral organs continuously forming at the meristem. Therefore, mechanisms controlling the formation, maintenance, and development of a meristem will be a key to understanding the body plan of higher plants. Genetic analyses of filamentous flower (fil) mutants have indicated that FIL is required for the maintenance and growth of inflore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
427
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(443 citation statements)
references
References 29 publications
13
427
1
2
Order By: Relevance
“…In Arabidopsis, establishment of abaxial identity further requires the activities of members of the YABBY and AUXIN RESPONSE FACTOR (ARF) families (Sawa et al 1999;Siegfried et al 1999;Pekker et al 2005). The YABBY genes FILAMENTOUS FLOWER (FIL) and YAB3 act, at least in part, downstream of the HD-ZIPIII and KAN genes, whereas ARF3/ETT and ARF4 affect organ polarity through a distinct pathway (Sawa et al 1999;Siegfried et al 1999;Kumaran et al 2002;Pekker et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, establishment of abaxial identity further requires the activities of members of the YABBY and AUXIN RESPONSE FACTOR (ARF) families (Sawa et al 1999;Siegfried et al 1999;Pekker et al 2005). The YABBY genes FILAMENTOUS FLOWER (FIL) and YAB3 act, at least in part, downstream of the HD-ZIPIII and KAN genes, whereas ARF3/ETT and ARF4 affect organ polarity through a distinct pathway (Sawa et al 1999;Siegfried et al 1999;Kumaran et al 2002;Pekker et al 2005).…”
mentioning
confidence: 99%
“…The YABBY genes FILAMENTOUS FLOWER (FIL) and YAB3 act, at least in part, downstream of the HD-ZIPIII and KAN genes, whereas ARF3/ETT and ARF4 affect organ polarity through a distinct pathway (Sawa et al 1999;Siegfried et al 1999;Kumaran et al 2002;Pekker et al 2005). ARF3/ETT is expressed more broadly than ARF4, but both transcription factors colocalize in the abaxial domain of leaf primordia, where they act in combination with KAN proteins to promote abaxial fate (Pekker et al 2005).…”
mentioning
confidence: 99%
“…The maize and Arabidopsis yabby genes may share a role in mediating lateral outgrowth along the adaxial/abaxial boundary (Eshed et al 2004;Juarez et al 2004a). However, the Ara- bidopsis YABBY genes also specify abaxial fate, and this function is not conserved in maize (Sawa et al 1999;Siegfried et al 1999;Kumaran et al 2002). Moreover, the miRNA loci involved in adaxial/abaxial patterning have diverged between Arabidopsis, rice, and maize.…”
Section: Discussionmentioning
confidence: 99%
“…Once this adaxial/abaxial polarity is established, it is interpreted by other downstream genes that lead to the differentiation of adaxial and abaxial specific cell types and to mediolateral blade outgrowth at the adaxial/abaxial boundary (Waites and Hudson 1995). Among these are the YABBY genes, a third family of transcriptional regulators, that act at least in part downstream of the HD-ZIPIII and KAN genes and are required for abaxial cell fate and lamina expansion (Sawa et al 1999;Siegfried et al 1999;Eshed et al 2001Eshed et al , 2004Kumaran et al 2002).…”
Section: Establishment Of Polarity In Developing Leavesmentioning
confidence: 99%
“…Hamilton et al ͑1996͒ reported stable integration of 150 kb of human DNA in the tobacco genome by Agrobacterium-mediated transformation with a binary BAC vector. A TAC ͑transformation-competent artificial chromosome͒ binary vector was used for Agrobacterium-mediated transformation of Arabidopsis with large DNA fragments ͑Liu et al 1999; Sawa et al 1999;Sato et al 2001͒. Biolistic transformation with whole BAC DNA offers an alternative method for transferring large DNA fragments into plant genomes.…”
Section: Introductionmentioning
confidence: 99%